Perceived social support buffers the consequences of internalized negativity among individuals in consensual non-monogamous relationships - Rodrigues, D. L.; Brooks, T. R.; Balzarini, R. N.; Moors, A. C. (Journal of Sex Research, 2026)
Departures from monogamy are socially discouraged and met with negative judgments, and being a target of stigmatization has consequences for the way individuals in consensual non-monogamous (CNM) relationships connect to others, including their partner(s). However, social support seems to be an important factor associated with increases in wellbeing and relationship quality. Aligned with this reasoning, results of a cross-sectional study showed that participants in CNM relationships who endorsed more internalized negativity reported less commitment to partner one (P1), less disclosure of their relationship agreement to others, as well as less acceptance and more secrecy toward P1 and partner two (P2). Results further showed that perceiving more social support was associated with more commitment to P1, less disclosure to people from the extended social circle, and more acceptance of the relationship with P1 and P2 among participants with higher internalized negativity. Perceiving more social support was also associated with more disclosure to people from the close social circle, as well as more acceptance and less secrecy toward the relationship with P1 and P2 among participants with lower internalized negativity. These results demonstrate that relationships embedded in social contexts of support can be a protective factor, even for individuals who report higher internalized negativity. Hence, for individuals in CNM relationships, fostering a positive and supportive social network seems to increase positive personal and relationship outcomes.